Implementasi Mesin Pencacah Plastik pada Bank Sampah di Maccini Sombala Kota Makassar - Syahid, Muhammad; Amme, Rudi; Salam, Nasaruddin; Piarah, Wahyu H; Tarakka, Rustan; Djafar, Zuriyati; Jalaluddin, Jalaluddin; Arfandy, Arfandy; Kasim, Lukman (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
The process of recycling plastic waste is one way of processing plastic waste. Plastic waste in the form of plastic bottles and cups has a high selling value when it is recycled. The Paraikatte Rong waste bank in Makassar City has been in the plastic waste processing business for 5 years. This waste bank only collects and sorts plastic waste due to the unavailability of plastic chopping machines that can help the plastic waste recycling process. Therefore, the Community Service Team of the Department of Mechanical Engineering, Faculty of Engineering, Hasanuddin University, with the implementation of appropriate technology designed and built a plastic chopping machine for the Paraikatte Rong waste bank. The method used is to conduct training on the use and maintenance of a plastic chopping machine. The purpose of this service is for the waste bank to carry out the recycling process optimally and efficiently so as to increase the economic value of plastic waste. The scissor system for chopping plastic is applied to the chopping machine so that the chopping results are smoother. The chopping machine consists of 3 dynamic blades and 2 static blades which can be adjusted to the density of the blades. This machine has a capacity of 100 kg/hour using a 7.5 hp petrol engine. The success of this community service activity can be seen from the increase in public understanding based on survey results where the total level of understanding/very understanding of the benefits of selecting plastic waste has increased from 35% to 52.6%. The operation of the plastic chopping machine has increased from 55% to 80%. The maintenance of the plastic chopping machine has increased from 53% to 87%.